The interface mixing layer and the tidal dynamics at the eastern part of the Strait of Gibraltar. - García-Lafuente, Jesús; Bruque Pozas, Elisa; Sánchez-Garrido, José Carlos; Sannino, Gianmaria; Sammartino, Simone (Elsevier, 2013)
A non-hydrostatic numerical model forced by tides has been adapted to the Strait of Gibraltar area to inves- tigate the dynamics of the interface layer in the eastern part of the strait, namely the area that extends from the main sill of Camarinal to the eastern exit of the strait. The model reproduces the tidal oscillations of the interface thickness and the mean depth, showing that the westward barotropic tide raises the interface and reduces its thickness, thus being the physical mechanism that re-stratifies the water column. Several process- es are involved in the thickening and sinking tidal phase of the interface: (1) the eastward horizontal advec- tion from Tangier basin, located west of Camarinal sill, where the huge dissipation associated with hydraulic transitions generates a remarkable mixing layer, (2) entrainment as the interface waters progress towards the Mediterranean Sea and (3) internal friction associated with the large amplitude internal waves radiated into the Mediterranean. Some biologically-related implications of the interface dynamics are also examined.
Keywords: Oleaje - Modelos matemáticos; Oceanografía; Alborán; Numerical model; Internal waves; Alboran Sea